The Development of the Three Pillars of Social Work Profession and its Resilience in Estonia - Sirotkina, Reeli (Socialinė teorija, empirija, politika ir praktika, 2025)
During the last thirty years, the Baltic states have come through dramatic and intense changes to develop their social work and social policy according to the examples of the Western welfare states. Regardless of the changes we have all come through during the contemporary history, the identity of the three Baltic countries is considerably different. This article draws attention to the Estonian pathway of social work development by looking at the development of the science of social work, the higher education in social work, and the practice of social work during the period of 1991–2022. By looking back at how social work became professionalised, and by analysing the critical incidents that have shaped this process, it is possible to strengthen both the nation’s collective social resilience and the professional resilience and development of social work as a discipline. The aim of this article is to show the main shifts and milestones during these years on the road of professionalisation of the social work science in Estonia while looking at the resilience of the profession which was co-created in the social work practice, research, and higher education. The article is based on the author’s postgraduate thesis “From a Helping to an Empowering Profession – the Process of Social Work Professionalisation in Estonia” defended at the University of Helsinki in 2024 highlighting the aim of the research, main theoretical concepts, reflection of being both an insider and an outsider during the study, along with the main results with discussion.